Modern to Ancient Barrier Island Dimensional Comparisons: Implications for Analog Selection and Paleomorphodynamics - Mulhern, Julia S.; Johnson, Cari L.; Martin, John M. (Frontiers in Earth Science, 2019)
Ancient barrier islands are poorly understood relative to other clastic depositional environments, despite being prominent features along modern coastlines and important for understanding transgressive shoreline deposits. A new dataset of ancient barrier island dimensions (n=83 examples) addresses this knowledge gap with a quantitative analysis of barrier island sand body dimensions including thickness (vertical), length (shore-parallel direction), and width (shore-perpendicular direction). This dataset of barrier island deposits was compared to planform measurements made for modern islands (n=274), to investigate possible scaling relationships and other aspects of modern to ancient linkages. These measurements are nuanced and challenging to perform, and first-pass comparisons show that modern barrier islands should not be used as direct analogs for ancient systems. Nevertheless, results emphasize key depositional and preservation processes, and the dimensional differences between deposits formed over geologic versus modern time scales. Using the methods outlined herein, barrier island deposits appear to be 2-5x longer (p50 modern = 10.7 km; p50 ancient = 20.0 km), and 6-15x wider (p50 modern = 1.2 km; p50 ancient = 7.3 km) than modern barrier islands. We interpret the results to indicate that ancient barrier islands are time-transgressive deposits recording vertical amalgamation, and barrier island growth by lateral accretion, and progradation. When comparing single barrier islands, thickness measurements do not vary systemically between modern and ancient examples, suggesting that local accommodation dictates barrier island thickness as a preservation control. Gross length, width, and thickness measurements are too coarse for robust paleomorphodynamic calculations, therefore more detailed sub-environment analysis (e.g., upper shoreface delineation), with improved facies models, is required before rigorous quantifications can be generated. However, these initial comparisons do show scaling trends between length and width which could be leveraged, with caution, in the interim. As sea levels continue to rise, understanding barrier island motion and preservation will be central to predicting coastal change. <Abstract 303 words> Keywords: paleomorphodynamics, barrier island, scaling relationships, accommodation, shallow marine, dimension prediction, modern analog, reservoir, transgressive